Evaluation of professional satisfaction of audiologists working in Türkiye based on their personality characteristics and sector of work - Çelikgün, Bahtiyar; Büyükkal, Furkan; Minga, Recep; Ölçek, Gül (Frontiers in Psychology, 2024)
Purpose This study investigates the relationship between audiologists' personality traits and professional satisfaction. Design Big Five-50 Personality Traits and Professional Satisfaction Scale was used to examine the relationship between audiologists' personality traits and professional satisfaction. Statistical analyzes were performed with SPSS and AMOS programs. Study example This study examines 167 audiologists who completed a minimum of an undergraduate program in audiology before the professional field. Results The results of confirmatory factor analysis indicate that both scales are reliable and valid. There is a significant relationship between extraversion, agreeableness, conscientiousness, and emotional stability and occupational satisfaction. However, there is no significant relationship between intelligence/imagination and professional satisfaction. Conclusions Extraversion, agreeableness, conscientiousness, emotional stability/neuroticism affect job satisfaction. Understanding these dynamics can inform strategies that will increase the professional wellbeing and productivity of audiologists.